An auto‐reclosing scheme for DC circuit breaker in VSC‐HVDC transmission system. Issue 16 (10th December 2018) - Wang, Yuan; Wang, Yuhong; Liu, Chengzhuo; Yang, Liwen
Abstract : When a DC line fault happens, the converter will be blocked instantly. This leads to an interruption of power transmission and influences the stability of DC and AC systems. To avoid the blocking of converters, this paper presents a novel protection scheme for VSC‐HVDC system, which consists fault isolation and auto‐reclosing of DC circuit breaker (DCCB). First, this paper coordinates the protective actions of converters and DCCB. The DC line fault is cut immediately by DCCB while the blocking signal of converter is isolated during the fault. Second, since the faults of long overhead transmission DC lines are mostly transient, an auto‐reclosing strategy is developed. The emphasise of this part, which includes fault discrimination and time sequences, between DCCB and converter is elaborated, and the value of reclosing delay is derived by analysing the charging and discharging characteristics of capacitor paralleled with converter. Finally, the protection scheme is evaluated by overcurrent, overvoltage, and recovery time of DC system, and simulation results of a point‐to‐point VSC‐HVDC transmission system proves its validity.